’En México, desde que usted entra... ¿de dónde tenemos para pagar a los policías?’ Institutional Machismo Affecting Migrant Women Heading North - López, María (PARTECIPAZIONE E CONFLITTO, 2025)
In 2023, Mexico was a transit and destination country for more than 700,000 undocumented migrants, the highest number ever recorded. Many of them are women and girls. While both men and women are exposed to violence on their journey, undocumented migrant women experience specific forms of violence and discrimination at the hands of migration guards, workers in state detention centres and migrant shelters, and bureaucrats. Drawing on concepts of male chauvinism, institutional violence and state violence along the migration route, and feminicidal violence, as well as data collected in a migrant shelter in Mexico City in 2023, this article focuses on institutional machismo as a set of violent norms by state officials, migration agents and shelter workers that exacerbate the dangers of undocumented women’s journeys and jeopardise their ability to overcome the gender values they have learned. This article also shows how women’s narratives of the journey reveal that some women have begun to articulate a more egalitarian understanding of gender roles. For them, the migration journey becomes a transformative experience from which they emerge empowered.